PHENOMENON OF ATYPICAL DNA COMETS - Zhanataev, A K; Anisina, E A; Chayka, Z V; Miroshkina, I A; Durnev, A D (T͡S︡itologii͡a, 2017)
The phenomenon of atypical DNA comets in experiments using DNA comet assay is described and illustrated. The current hypotheses explaining the nature of atypical DNA comets and own vision of the issue are considered. The practical importance of the registration of atypical DNA comets in assessing the genotoxicity is discussed.